Paired‐pulse facilitation at recurrent Purkinje neuron synapses is independent of calbindin and parvalbumin during high‐frequency activation. (7th June 2013) - Bornschein, Grit; Arendt, Oliver; Hallermann, Stefan; Brachtendorf, Simone; Eilers, Jens; Schmidt, Hartmut
Key points Endogenous Ca2+ binding proteins such as calbinding‐D28k (CB) and parvalbumin (PV) are considered important regulators of short‐term synaptic plasticity. Cerebellar Purkinje neurons express large amounts of CB and PV and are laterally connected by inhibitory synapses that show paired‐pulse facilitation (PPF) during high‐frequency activation. We report quantal synaptic release parameters of these synapses in wild‐type and in CB and PV knock‐out mice; evidence is provided that these synapses operate at nanodomain influx‐release coupling. We find that PPF is independent of CB and PV, using a combination of paired electrophysiological recordings, synaptic Ca2+ imaging and numerical computer simulations. Our results suggest that PPF during high‐frequency activation results from slow Ca2+ unbinding from the sensor for transmitter release, which is reminiscent of the 'active Ca2+' mechanism of PPF suggested by Katz and Miledi in 1968. Abstract Paired‐pulse facilitation (PPF) is a dynamic enhancement of transmitter release considered crucial in CNS information processing. The mechanisms of PPF remain controversial and may differ between synapses. Endogenous Ca2+ buffers such as parvalbumin (PV) and calbindin‐D28k (CB) are regarded as important modulators of PPF, with PV acting as an anti‐facilitating buffer while saturation of CB can promote PPF. We analysed transmitter release and PPF at intracortical, recurrent Purkinje neuron (PN) to PN synapses, which show PPF during high‐frequency activation (200 Hz) and strongly express both PV and CB. We quantified presynaptic Ca2+ dynamics and quantal release parameters in wild‐type (WT), and CB and PV deficient mice. Lack of CB resulted in increased volume averaged presynaptic Ca2+ amplitudes and in increased release probability, while loss of PV had no significant effect on these parameters. Unexpectedly, none of the buffers significantly influenced PPF, indicating that neither CB saturation nor residual free Ca2+ ([Ca2+]res) was the main determinant of PPF. Experimentally constrained, numerical simulations of Ca2+‐dependent release were used to estimate the contributions of [Ca2+]res, CB, PV, calmodulin (CaM), immobile buffer fractions and Ca2+ remaining bound to the release sensor after the first of two action potentials ('active Ca2+') to PPF. This analysis indicates that PPF at PN–PN synapses does not result from either buffer saturation or [Ca2+]res but rather from slow Ca2+ unbinding from the release sensor.